Transport proteins of parasitic protists and their role in nutrient salvage - Dean, Paul; Major, Peter; Nakjang, Sirintra; Hirt, Robert P.; Embley, T. Martin (Frontiers in Plant Science, 2014)
The loss of key biosynthetic pathways is a common feature of important parasitic protists, making them heavily dependent on scavenging nutrients from their hosts. This is often mediated by specialised transporter proteins that ensure the nutritional requirements of the parasite are met. Over the past decade, the completion of several parasite genome projects has facilitated the identification of parasite transporter proteins. This has been complemented by functional characterisation of individual transporters along with investigations into their importance for parasite survival. In this review, we summarise the current knowledge on transporters from parasitic protists and highlight commonalities and differences in the transporter repertoires of different parasitic species, with particular focus on characterised transporters that act at the host-pathogen interface.